REFINEMENT AND GRANULATING OF COHERENT-GRANULAR MATERIALS IN MACHINES OF ROLL TYPE - E. B. Lozhechnikov; A. K. Gavrilenja; S. G. Azizbekjan; S. V. Lasankin (Литьë и металлургия, 2006)
The way of selective break of heterogeneous compositions, in particular slags of copper-smelting production and also granular metal-containing powder materials, is based and developed. Calibration of the rolls, providing contrilled granulating of metal-containing powders by rolling.